Paclitaxel-Eluting Balloon vs. Standard Angioplasty to Reduce Recurrent Restenosis in Diabetic Patients With In-Stent Restenosis of the Superficial Femoral and Proximal Popliteal Arteries: The DEBATE-ISR Study. (February 2014) - Liistro, Francesco; Angioli, Paolo; Porto, Italo; Ricci, Lucia; Ducci, Kenneth; Grotti, Simone; Falsini, Giovanni; Ventoruzzo, Giorgio; Turini, Filippo; Bellandi, Guido; Bolognese, Leonardo
Purpose: To test the ability of a drug-eluting balloon (DEB) to reduce recurrent in-stent restenosis (ISR) in diabetic patients with femoropopliteal stents. Methods: A prospective all-comers study [Drug-Eluting Balloon in Peripheral Intervention for In-Stent Restenosis (DEBATE-ISR); ClinicalTrials.gov identifier NCT01558531] of symptomatic diabetic patients with femoropopliteal ISR undergoing treatment with paclitaxel-eluting balloons was designed to compare their 12-month recurrent restenosis rate with that of historical diabetic controls. From January 2010 to December 2011, 44 consecutive diabetic patients (32 men; mean age 74±11 years) were treated with DEBs and enrolled in the study. The control group comprised 42 diabetic patients (23 men; mean age 76±7 years) treated with a conventional balloon for femoropopliteal ISR from 2008 to 2009. Results: No significant differences in terms of clinical, angiographic, or procedural characteristics were observed between the study groups. Lesion length was 132±86 mm in the DEB group vs. 137±82 mm in the BA group. Procedural success, defined as a residual stenosis <30% in the restenotic segment (stent +5 mm at proximal and distal edges), was obtained in all treated lesions. At 1-year follow-up, 6 patients died (3 in each group), and 1 patient in the BA group underwent major amputation. Recurrent restenosis, assessed by angiography (66%) or ultrasound (34%), occurred in 8/41 (19.5%) patients in the DEB group vs. 28/39 (71.8%) in the BA group (p<0.001). Target lesion revascularization for symptomatic recurrent restenosis was performed in 6/44 (13.6%) patients in the DEB vs.13/42 (31.0%) in the BA group (p=0.045). Conclusion: Using DEB for treating femoropopliteal ISR led to a significant reduction in recurrent restenosis and repeat angioplasty at 1-year follow-up as compared to historical controls.